2015
DOI: 10.1007/s00404-015-3670-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of treatment based on single high blood glucose in gestational diabetes screening on maternal and neonatal complications

Abstract: Although the treatment of mild gestational diabetes could not significantly decrease severe neonatal outcomes, it did significantly reduce the risk of hyperbilirubinemia and its subsequent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We included eight publications not included in any previous published review. One compared metformin and insulin 31 ; one, glibenclamide and insulin 32 ; four, packages of care with routine care 33–36 ; and two compared different dietary modification interventions. 37 38 Six of these trials were reported after the search dates of the previous reviews and were published in 2014 or 2015; the remaining two trials (dietary modification interventions or packages of care) did not fulfil other review’s inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included eight publications not included in any previous published review. One compared metformin and insulin 31 ; one, glibenclamide and insulin 32 ; four, packages of care with routine care 33–36 ; and two compared different dietary modification interventions. 37 38 Six of these trials were reported after the search dates of the previous reviews and were published in 2014 or 2015; the remaining two trials (dietary modification interventions or packages of care) did not fulfil other review’s inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Nine trials compared glibenclamide with insulin ( table 3 ). 32 67–74 Figure 2E shows the RRs of dichotomous outcomes, suggesting that insulin may be relatively more effective than glibenclamide in reducing the risk of several adverse outcomes; CIs are wide and include the null value however. There was no difference between insulin and glibenclamide for continuous outcomes ( figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that the group diagnosed with the IADPSG criteria had only a decreased risk of neonatal hyperbilirubinemia (odds ratio (OR) 0.25, 95% CI 0.68–0.88). 61 Another RCT performed in 1000 pregnant women compared the incidence, maternal and fetal outcomes of GDM diagnosed using the one-step screening with IADPSG criteria versus two-step screening with GCT and diagnosis based on a 100g OGTT with CC criteria. 62 They found that the incidence of GDM using IADPSG criteria almost doubled (19.23% vs 11.81%, p=0.0001), and that maternal and neonatal outcomes were comparable in both groups except for lower rates of preterm delivery (11.6% vs 24.1%, relative risk (RR) 2.08, 95% CI 1.01–4.2, p = 0.046) and neonatal hypoglycemia (7.4% vs 29.31%, RR 3.98, 95% CI 1.75–9.01, p = 0.003) when using IADPSG criteria.…”
Section: Overview Of the Included Publicationsmentioning
confidence: 99%
“…It is estimated that 85% of the embryos by assisted reproductive techniques do not implant after transfer. [ 6 7 8 ] Studies have shown that different methods have been used to manage recurrent implantation failures, but there is little consensus on the most effective ones. The common methods used include blastocyst transmission, pre-transplant genetic screening, hatching, co-culture system, sequential transmission, hysteroscopy, endometrial scratch, salpingectomy, additional ET, egg donation, and immunotherapy, but there is no proven evidence for these treatments.…”
Section: Introductionmentioning
confidence: 99%